2020
DOI: 10.1021/acs.analchem.0c01153
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ultralow Level 135Cs and 135Cs/137Cs Ratio in Environmental Samples by Chemical Separation and Triple Quadrupole ICP-MS

Abstract: An analytical method was developed for the determination of ultralow level 135 Cs in environmental samples by chromatographic separation of cesium with AMP-PAN and AG50W-X8 columns and sensitive measurement of cesium isotopes with triple quadrupole inductively coupled plasma mass spectrometry (ICP-MS/MS). Cesium was simply released by acid leaching using aqua regia from environmental solid samples and preconcentrated on AMP-PAN column. The cesium adsorbed on the column was effectively eluted with NH 4 Cl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…5, N2O, CO2, and CH4 were also used in multiple reports instead of the default cell gases. By using N2O as the cell gas, the production rate of the oxide ions of (Mn, Fe, Ni, Cu, Zn, and Se), 1 Sr, 3,68 Br, 8 Ba, 23 (Ge, Eu, Yb) 29 and Ra, 28,45 is greatly improved in comparison to those obtained by using O2 as the cell gas. This feature provides a higher sensitivity and/or a better separation of spectral interference.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
See 3 more Smart Citations
“…5, N2O, CO2, and CH4 were also used in multiple reports instead of the default cell gases. By using N2O as the cell gas, the production rate of the oxide ions of (Mn, Fe, Ni, Cu, Zn, and Se), 1 Sr, 3,68 Br, 8 Ba, 23 (Ge, Eu, Yb) 29 and Ra, 28,45 is greatly improved in comparison to those obtained by using O2 as the cell gas. This feature provides a higher sensitivity and/or a better separation of spectral interference.…”
Section: Reaction Gases Used In the Measurement By Icp-qms/qmsmentioning
confidence: 99%
“…Research fields and objectives. The research fields of the above references covered biology, 1-15 energy, 16 environment, 9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] food/medical, 10-12,25-27,33-40 geology, 28,41-47 material, [48][49][50][51][52][53][54][55][56][57][58][59][60] and radionulide, 4,[22][23][61][62][63][64][65][66][67][68][69][70][71] respectively. In addition to these conventional elemental analysis topics, a study on the gas phase catalytic reaction has also been reported by using the reaction cell of ICP-QMS/QMS as the in-situ reaction field.…”
Section: References Investigatedmentioning
confidence: 99%
See 2 more Smart Citations
“…The low abundance of 135 Cs with its high isobaric background of 135 Ba makes it difficult to detect, also for mass spectrometric approaches. Due to this difficulty, most studies presenting 135 Cs/ 137 Cs ratios were performed on water with 135,137 Cs/ 133 Cs ratios of 10 −8 or higher, i.e., close to sources of contamination (Zhu et al, 2020a). Two recent studies show first results on 135 Cs concentration in general seawater from the west coast of Greenland.…”
Section: Introductionmentioning
confidence: 99%